Coastal resilience and shoreline dynamics: assessing the impact of a hybrid beach restoration strategy in Puducherry, India - Benhur, Judha; Vendhan, Mullai; Kumar, Phani; Janagiraman, Ramkumar (Frontiers in Marine Science, 2024)
Puducherry, a Union Territory of India, has been strongly affected by severe erosion after the construction of the Puducherry port in 1989. To mitigate this cause, the National Institute of Ocean Technology, Chennai, and the Puducherry government implemented a beach restoration strategy involving a hybrid solution in 2017 for coastal protection/stabilization and the restoration of the lost beach. The strategy involved deploying a steel reef into the nearshore sea and implementing beach nourishment processes. To monitor the coastal morphological changes after implementing the coastal protection strategy, the Digital Shoreline Analysis System, was adopted to calculate the rate of shoreline change statistics for the years 2016 to 2022. It uses spatio-temporal shoreline positions from multi-temporal satellite imagery. The shorelines are extracted from the Sentinel-2A satellite images by a Normalized Differential Water Index based semi-automated model. Statistical parameters in DSAS analyze the shorelines to determine the shoreline changes in this area. The results reveal the remarkable resilience of a newly restored beach, where the linear regression rate statistics in Zone A show an average accretional rate of 2.92m/yr. Alternatively, Zone B exhibits an average erosion rate of -0.23m/yr, with intermittent sandy beaches experiencing maximum erosion rates of -1.63m/yr. The influence of longshore current direction and sediment transport on shoreline movement is evident in seasonal analysis, with shoreline development and recession primarily observed near shore protection structures. The study’s outcome provides valuable insights for coastal management, offering a reliable approach for shoreline monitoring post-implementation of mitigation projects.